Perianal Tuberculosis: A Case Report and a Review of the Literature - K. Ibn Majdoub Hassani; S. Ait Laalim; I. Toughrai; K. Mazaz (Case Reports in Infectious Diseases)
Extra pulmonary tuberculosis accounts for less than 15% of all cases of tuberculosis whereas the Intestinal one constitutes less than 1% of the extrapulmonary forms of the disease. The lesions of abdominal organs are more common while they rarely occur in the anoperineal area for the spread of the disease to the anus is extremely rare. We report a case of a 37-year-old male patient with large bilateral infected perianal tubercular ulcerations as well as pulmonary and peritoneal tuberculosis. The treatment was both surgical and medical and the therapy lasted for seven months. After six months from the beginning of the treatment, the lesion had totally disappeared and there is still no recurrence after one year of followup. Tuberculosis should generally be taken into consideration in the differential diagnosis of the ulcerative lesions of the anal and perianal regions for these lesions do occur in the said areas despite their rarity. The treatment is usually both surgical and medical so as to get excellent results.